Electrohydrodynamic drying of food: New insights from conjugate modeling. (10th October 2018) - Defraeye, Thijs; Martynenko, A.
Abstract: Electrohydrodynamic (EHD) drying is a non-thermal technology with promising perspectives to dehydrate heat-sensitive materials such as foods. With EHD drying, corona discharge is used to generate airflow, which enhances convective drying of the food product. Further development and upscaling of this technology are hindered by a lack of insight in both the airflow and the dehydration process inside the material during drying. This study is the first to develop a conjugate continuum model which couples EHD-generated airflow directly to the convective heat transfer and moisture removal from the food. For the wire-to-plate configuration with impinging flow, the impact of different geometrical and operational parameters (wire radius, distance to collector electrode, emitter voltage) on the EHD-driven airflow and resulting drying kinetics is quantified. The fruit drying time is found to increase linearly with increasing distance between electrodes or increasing emitter electrode radius, but decreases in a non-linear way with increasing voltage between the electrodes. For other emitter-collector configurations, where airflow passes around the fruit, such as wire-to-mesh, wire-to-plate, wire-to-wires and wire-to-parallel plates, significant differences in drying kinetics were quantified. Such configurations provide better perspectives towards upscaling to dry large amounts of products uniformly. Of all tested configurations, the wire-to-mesh configuration provided the highest drying rate. Placing the fruit on a mesh also showed to be advantageous since the fruit can be dried more uniformly. The developed conjugate approach has the distinct advantage that the impact of EHD process parameters and geometrical configurations on the drying rate can be quantified very swiftly. Such modeling approach is thereby a valuable tool for further optimization of EHD drying technology towards industrial implementation. Graphical abstract: Image 1 Highlights: This conjugate model is the first to couple ionic wind to food dehydration. Dependency of drying time on voltage, electrode distance and radius is quantified. The conventional wire-to-plate configuration is not the best to achieve fast and uniform drying. The wire-to-mesh configuration shows the highest EAD-driven food drying rate. Placing food on a mesh is preferred to dry large amounts of products uniformly.